Incidence of prostate adenocarcinoma in transurethral resection of the prostate patients - Yahia Ghazwani; Abdullah Alhaider; Rakan Aldharab; Faisal Aldumiaikhi; Nasser Albogami; Abdulaziz Alathel; Ali Alothman; Raghib Abusaris; Mosaad Alshahwan; Fahad Alhamad; Ziyad Aljaafri; Khalid Alduraibi (Urology Annals)
Objective: This study aims to present the prevalence of incidental prostate cancer (IPCa) based on pathology reports of prostate tissue chips following transurethral resection of the prostate (TURP), as well as to assess cancer’s stage, associated risk factors, and treatment modalities upon diagnosis. Methods: This cross-sectional retrospective study included patients who underwent TURP between 2015 and 2023. Patients with a preexisting PCa diagnosis were excluded, resulting in the analysis of 418 patients. Data collected encompassed basic characteristics, personal history of malignancies unrelated to IPCa, prostate volume, and prostate-specific antigen (PSA) levels. IPCa cases were identified through the pathology reports of the prostatic chips. In addition, cancer stage, Gleason score, treatment choices, and outcomes were documented for IPCa cases. Results: Among the 418 patients who underwent TURP, 35 were diagnosed with IPCa, yielding a prevalence rate of 8.4% (95% confidence interval: 5.7%–11.0%). Of these cases, 13 (37.1%) exhibited metastatic disease, and 4 (11.8%) resulted in patient mortality. IPCa patients were found to have significantly higher PSA levels and smaller prostate volumes. Multivariable logistic regression analysis indicated that elevated PSA density, ischemic heart disease, and chronic kidney disease, significantly influenced the likelihood of IPCa (P < 0.05). Mann–Whitney testing revealed that patients with metastatic disease had a median Gleason score of 9, whereas those with localized disease had a median score of 7 (P < 0.001). Conclusion: Our study disclosed an IPCa prevalence of 8.4%, with IPCa patients exhibiting elevated PSA levels and reduced prostate volumes, suggesting that PSA density is a valuable tool for evaluating patients with borderline PSA levels.